2023
DOI: 10.1063/5.0124834
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic electron heating in an electron cyclotron resonance thruster with magnetic nozzle

Abstract: In a grid-less electron cyclotron resonance plasma thruster with a diverging magnetic nozzle, the magnitude of the ambipolar field accelerating the positive ions depends on the perpendicular energy gained by the electrons. This work investigates the heating of the electrons by electromagnetic waves, taking their bouncing motion into account in a confining well formed by the magnetic mirror force and the electrostatic potential of the thruster. An electromagnetic particle-in-cell code is used to simulate the pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Wachs et al [26] demonstrated that this effect is due to inelastic electron-neutral collisions in the thruster plume, which consume a significant part of the jet power and ultimately decrease the ion energy. Even though the mean free path of an electron is large compared to the size of the plume for pressure levels presented here (from 33 km at 1.2 × 10-7 mbar to 202 m at 2.0 × 10-5 mbar), the pendular motion of a part of the electron population trapped in the plume [34] and the large size of the acceleration region in the plume explain this result [26].…”
Section: Facility Effectsmentioning
confidence: 58%
See 1 more Smart Citation
“…Wachs et al [26] demonstrated that this effect is due to inelastic electron-neutral collisions in the thruster plume, which consume a significant part of the jet power and ultimately decrease the ion energy. Even though the mean free path of an electron is large compared to the size of the plume for pressure levels presented here (from 33 km at 1.2 × 10-7 mbar to 202 m at 2.0 × 10-5 mbar), the pendular motion of a part of the electron population trapped in the plume [34] and the large size of the acceleration region in the plume explain this result [26].…”
Section: Facility Effectsmentioning
confidence: 58%
“…The H2020 MINOTOR project aims at increasing the Technology Readiness Level (TRL) of the ONERA thruster prototype. All the different aspects of the thruster development were tackled: prototype optimization and testing, numerical simulation tools development [32][33][34], Power Processing Unit (PPU) development, system impact assessment and scaling up with the development of a 200 W thruster. The present paper recounts part of the results obtained during the prototype optimizations and testing studies.…”
Section: Introductionmentioning
confidence: 99%